THE INFLUENCE OF PERCEIVED RISK ON PURCHASE POSTPONEMENT OF PRIVATE LABEL BRAND PRODUCT AT HYPERMART - Wijaya, Steven; Mekel, Peggy A.; Tumiwa, Johan (FEB Universitas Sam Ratulangi Manado, 2014)
Marketers nowdays focus on product attributes to satisfy the consumer needs and wants, most of them able to deliver the product value in consumer mind and success in triggering purchase decision, but unfortunately some marketers face the problem that consumer may perceived some risk on their product and can lead to purchase postponement by the consumer. The questions to be adressed in this research are,Â do consumers perceived risk exist on private label brand product offered by Hypermart with Value Plus trademark and do the perceived risk influence purchase postponement. The objectives of this research are to analyze the perceived risk factor in influencing purchase postponement of Hypermart private label brand product in Manado and identify which type of perveived risk that have the most significant effect on purchase postponement. Multiple Linear Regression Analysis choosen as the tool to reveal the associational of two or more variable in this research. From the examination of 100 respondents the research shows Perceived Risk factor which are Functional Risk, Physical Risk, and Financial Risk has significant effect on purchase postponement of Hypermart private label brand product. Therefore, Hypermart should be considering a strategy to minimize the risk perceived by consumer in order to trigger consumer not to postpone their purchase decision. Keywords: functional risk, physical risk, financial risk, purchase postponement